Analisis Tingkat Stres Pada Pasien Hemodialisa Di RSUD Arifin Achmad Provinsi Riau Di Masa Pandemi COVID-19 - Dendy Kharisna; Tengku Syahrizal; Veni Dayu Putri (STIKes Payung Negeri Pekanbaru, 2020)
The progression of kidney failure impacts on the deterioration of the patient's condition with the advent of various complications. As a result, patients have to be given various treatment therapies such as hemodialysis in order to survive. Hemodialysis (HD) aims to treat patient, however it also has negative effects on the patient's physical and psychological condition. In addition, the spread of covid-19 cases affects patients who have to keep doing HD on schedule. The purpose of this study was to analyze the stress level of patients undergoing hemodialysis at the Arifin Achmad Regional Hospital, Riau Province during the Covid-19 pandemic. This study used a quantitative descriptive approach with a cross-sectional design. The study sample consisted of 47 patients who underwent HD taken by accidental sampling. The instrument used was the Depression Anxiety Stress Scale 42 (DASS) questionnaire with a focus on the dimensions of stress. The univariate analysis used in this study is the frequency distribution. The results showed that most male respondents were 29 people (61.7%), aged> 45 years were 33 people (70.2%), and had HD> 6 months as many as 29 people (61.7%). Most respondents do HD twice a week with 27 people (57.4%) with a duration of HD> 4 hours as many as 25 people (53.2%). The results of the analysis also showed that most of the respondents experienced severe stress as many as 27 people (57.5%). Based on these results, it is recommended that HD officers be able to educate patients and empower peer groups to control or reduce patient stress levels.